The societal economic value of COVID-19 vaccines in the United States. (31st December 2022) - Kirson, Noam; Swallow, Elyse; Lu, Jessica; Mesa-Frias, Marco; Bookhart, Brahim; Maynard, Josie; Shivdasani, Yashna; Lefebvre, Patrick
Abstract: Aims: The COVID-19 pandemic has claimed the lives of more than 800, 000 people in the United States (US) and has been estimated to carry a societal cost of 16 trillion over the next decade. The availability of COVID-19 vaccines has had a profound effect on the trajectory of the pandemic, with wide-ranging benefits. We aimed to estimate the total societal economic value generated in the US from COVID-19 vaccines. Methods: We developed a population-based economic model informed by existing data and literature to estimate the total societal value generated from COVID-19 vaccines by avoiding COVID-19 infections as well as resuming social and economic activity more quickly. To do this, we separately estimated the value generated from life years saved, healthcare costs avoided, quality of life gained, and US gross domestic product (GDP) gained under a range of plausible assumptions. Results: Findings from our base case analysis suggest that from their launch in December 2020, COVID-19 vaccines were projected to generate 5.0 trillion in societal economic value for the US from avoided COVID-19 infections and resuming unrestricted social and economic activity more quickly. Our scenario analyses suggest that the value could range between 1.8 and 9.9 trillion. Our model indicates that the most substantial sources of value are derived from reduction in prevalence of depression (1.9 trillion), gains to US GDP (1.4 trillion), and lives saved from fewer COVID-19 infections (1.0 trillion). Limitations: Constructed as a projection from December 2020, our model does not account for the Delta or future variants, nor does it account for improvements in COVID-19 treatment. Conclusions: The magnitude of economic benefit from vaccination highlights the need for coordinated policy decisions to support continued widespread vaccine uptake in the US.